Determinants of performance of social control in municipal context - Marques Ferreira, Marco Aurelio; Sabioni Ferreira, Marjorie Angelica; Pineda Nebot, Carmen [UNESP] (Univ Castilla-la Mancha, Fac Ciencias Juridicas & Sociales, 2016)
This research was based on the theories of Public Administration and Citizen Engagement, investigating municipal characteristics that interfere in the participation of social control. Through the use of logistic regression and chi-square test on data from 853 cities of Minas Gerais, was presumed to point four important variables for the performance of social control: per capita income, youth population, male population and voters. The study reinforces arguments about the need for public management to consider the role of the multiple contexts in training programs that foster social control, aiming to provide different actions especially for those cities that have low participative action.
Keywords: Public Administration; Contextual aspects; Citizen Engagement